IP³ receptors and Ca²+ signals in adult skeletal muscle satellite cells in situ. - Colasante, Cesare; Molgó, Jordi; Adams, Dany S.; Jaimovich, Enrique (SABER ULA, 2005)
IP³ receptors and Ca²+ signals in adult skeletal muscle satellite cells in situ.(Molgó, Jordi, Colasante, Cesare, Adams, Dany S. and Jaimovich, Enrique.) Abstract In this short article we review muscle satellite cell characteristics and our studies in adult rodent muscle satellite cells in situ. Using confocal laser scanning microscopy and immunocytochemistry, a high level of receptor (IP3R) immunostaining was detected in satellite cells. These cells were identified by their peripheral position, their size, the shape of their nucleus, the paucity of the apparent cytoplasm, and the immunostaining with specific molecular markers such as a-actinin, the neural cell adhesion molecule (N-CAM) and desmin. High extracellular K+ (60 mM) induced long-lasting Ca²+; signals in satellite cells in situ. We suggest that electrical activity stimulates IP3-associated Ca²+; signals that could act in concert with signaling pathways triggered by growth factors and/or hormones. This paper is dedicated to the memory of Dr. Jeanne A. Powell.
Keywords: Medicina y Salud; Facultad de Medicina; Muscle satellite cells; Inositol 1,4,5-trisphosphate receptors; Intracellular Ca²+; Signal transduction; Laboratorio de Fisiología de la Conducta; Artículos